Some Properties of Extracellular Acetylxylan Esterase Produced by the Yeast Rhodotorula mucilaginosa - Lee, Hung (1987)
The red yeast Rhodotorula mucilaginosa produced an esterase that accumulated in the culture supernatant on induction with triacetin. The enzyme was specific for substrates bearing an O-acetyl group, but was relatively nonspecific for the rest of the molecule, which could consist of a phenol, a monosaccharide, a polysaccharide, or an aliphatic alcohol. The esterase was more active against acetylxylan and glucose β-d-pentaacetate than were a number of esterases from plant and animal sources, when activities on 4-nitrophenyl acetate were compared. The enzyme exhibited Michaelis-Menten kinetics and was active over a broad pH range (5.5 to 9.2), with an optimum between pH 8 and 10. In addition, the enzyme retained its activity for 2 h at 55°C. The yeast that produced the enzyme did not produce xylanase and, hence, is of interest for the production of acetylxylan esterase that is free of xylanolytic activity.